Assortative mating and epistatic mating‐trait architecture induce complex movement of the crow hybrid zone. (13th November 2021) - Metzler, Dirk; Knief, Ulrich; Peñalba, Joshua V.; Wolf, Jochen B. W.
Abstract: Hybrid zones provide a window into the evolutionary processes governing species divergence. Yet, the contribution of mate choice to the temporal and spatial stability of hybrid zones remains poorly explored. Here, we investigate the effects of assortative mating on hybrid‐zone dynamics by means of a mathematical model parameterized with phenotype and genotype data from the hybrid zone between all‐black carrion and gray‐coated hooded crows. In the best‐fit model, narrow clines of the two mating‐trait loci were maintained by a moderate degree of assortative mating inducing pre‐ and postzygotic isolation via positive frequency‐dependent selection. Epistasis between the two loci induced hybrid‐zone movement in favor of alleles conveying dark plumage followed by a shift in the opposite direction favoring gray‐coated phenotypes ∼ 1 200 generations after secondary contact. Unlinked neutral loci diffused near‐unimpeded across the zone. These results were generally robust to the choice of matching rule (self‐referencing or parental imprinting) and effects of genetic drift. Overall, this study illustrates under which conditions assortative mating can maintain steep clines in mating‐trait loci without generalizing to genome‐wide reproductive isolation. It further emphasizes the importance of the genetic mating‐trait architecture for spatio‐temporal hybrid‐zone dynamics.